Upper gastro-intestinal bleeding: Aetiology and demographic profile based on endoscopic examination at Dhulikhel Hospital, Kathmandu University Hospital - Gurung, RB; Joshi, G; Gautam, N; Pant, P; Pokhrel, B; Koju, R; Bedi, TRS (Kathmandu University Medical Journal, 2010)
Background: The upper gastrointestinal bleeding (UGIB) is defined as bleeding within the intraluminal gastrointestinal tract from any location between the upper oesophagus to the duodenum at the ligament of Treitz. It is one of the important medical emergencies worldwide. Objective: The objective of this study is to study the aetiology of upper gastrointestinal bleeding based on endoscopic examination findings in patients of various demographic characteristics. Materials and methods: This is a retrospective observational study. The endoscopic record book from 2007 January to 2009 October was reviewed for all the cases who underwent oesophago-gastro-duodenoscopic examination for upper GI bleeding. The clinico-epidemiological data of all the patients was reviewed and analyzed in concert with the aetiology of bleeding. Results: A total of 90 patients (58 males, 32 females; mean age 45.32+ 18.47 years) of upper gastrointestinal bleeding was studied and analyzed in terms of aetiology of bleeding and demographic profile. Among the ethnic groups, Aryan 46 (51%) was the most common ethnic group to have upper GI bleeding followed by Newars 24 (27%), Mongolians 16 (18%), Dalits 3 (3%) and others 1 (1%). Out of 90 patients, 47( 52.2%) cases was less than 45 years of age, 30(33.3%) of 46 to 65 age ; and 13(14.4 %) more than 65 years of age. Gastric ulcer 23(25.6%) was the most common endoscopic finding, followed by oesophageal varices 14 (15.6%), acute erosive/haemorrhagic gastropathy 11 (12.2%), duodenal ulcer 9(10%), growth 7(7.8%), vascular lesions 3(3.3%), Mallory-Weiss tear 1(1.1%), fundal varices 1(1.1%) and, no cause was identified in 21(23.3%) cases. The peptic ulcer bleeding was the most common finding in Aryan 22(47.9%), whereas oesophageal varices and growth were more common in Newar 7(29.2%) and 3 (12.5%) respectively. Conclusion: Peptic ulcer disease is the most common cause of upper GI bleeding which was most commonly found in Aryan population; followed by oesophageal varices and growth as second and third most common causes and were more prevalent in Newar and Mongolian people. Key words: Endoscopy; Peptic ulcer disease; Upper GI bleeding; Varices DOI: 10.3126/kumj.v8i2.3560 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 208-211